2019
DOI: 10.1039/c8ta09849b
|View full text |Cite
|
Sign up to set email alerts
|

Acid tolerant covalently functionalized graphene oxide for the selective extraction of Pd from high-level radioactive liquid wastes

Abstract: Covalently functionalized graphene oxides were explored as a promising material for the recycle of severely depleting highly demanded palladium (Pd) from strongly acidic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…The O 1s spectral profile was fitted using two Gaussian components at 531.3 and 532.6 eV. The lower energy peak, located at 531.3 eV corresponds to the oxygen of the OC–N amide group, and further confirms the covalent functionalization of the nanoparticles with the ethanolamine molecule . The higher energy peak, located at 532.6 eV, is assigned to the −OH groups of both CNPs and ethanolamine molecule. , …”
Section: Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The O 1s spectral profile was fitted using two Gaussian components at 531.3 and 532.6 eV. The lower energy peak, located at 531.3 eV corresponds to the oxygen of the OC–N amide group, and further confirms the covalent functionalization of the nanoparticles with the ethanolamine molecule . The higher energy peak, located at 532.6 eV, is assigned to the −OH groups of both CNPs and ethanolamine molecule. , …”
Section: Results and Discussionmentioning
confidence: 92%
“…The lower energy peak, located at 531.3 eV corresponds to the oxygen of the OC−N amide group, and further confirms the covalent functionalization of the nanoparticles with the ethanolamine molecule. 48 The higher energy peak, located at 532.6 eV, is assigned to the −OH groups of both CNPs and ethanolamine molecule. 49,50 Covalent functionalization of nanoparticles was further demonstrated monitoring the XP spectrum of CNPs-C 2 -OH in the N 1s binding energy region (see Supporting Information, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…Spent nuclear fuel producing high-level liquid wastes (HLLW) contains palladium that is extracted successfully. 122,123 These are the major harmful solid wastes. Developing an easy way to recycle this waste will be a good way to attain a green environment.…”
Section: Future Opportunitymentioning
confidence: 99%
“…It has been reported that the graphite-based PPy composite electrodes prepared using different chemical or electrochemical ways in the presence or absence of dopants on varying current collectors such as Au, Ni-foam, Ti, Ta, and carbonaceous materials operate commonly below the decomposition potential of water of $1.3 V in the aqueous electrolytes including NaCl, 9 KCl, 28,32 LiCl, 17 Na 2 SO 4 , 10 NaClO 4 , 49 LiClO 4 , 24 H 2 SO 4 , 11,25 and KOH. 50 The capacitances estimated from the charge-discharge curves at 5 mA cm À2 in Figure 6B In order to meet demands for practical applications further tests were made to evaluate the capacitor performance of the CF/GrO/PPy/AMPS(0.01) electrode by designing a two-electrode cell using the graphite plate as the counter electrode as well as assembling an asymmetric capacitor device with 1 cm  1 cm area.…”
Section: Comparison Of the Electrode Performances Of The Compositesmentioning
confidence: 99%